Gamma-aminobutyric acid (GABA) in the development of the paraventricular nucleus of the hypothalamus (PVN): implications for adult disease - Stratton, Matthew S., author; Tobet, Stuart, advisor; Amberg, Gregory, committee member; Bamburg, James, committee member; Mykles, Donald, committee member (Colorado State University. Libraries, 2012)
The paraventricular nucleus of the hypothalamus (PVN) is the final common regulator of the neuroendocrine stress response. Humans with depression or anxiety disorders display altered regulation of this system and females are more likely to suffer from these disorders than males. This work investigated embryonic development of the PVN to identify cellular processes that might occur incorrectly (preferentially in females) and predispose the individual to altered regulation of stress responses. GABA acts as a neurotrophic factor during development. As the embryonic PVN is ringed by GABA (absence of GABA in the PVN) and a receptor for GABA is enriched in the PVN, it was hypothesized that this molecule would direct PVN development. Embryonic development was altered in mice either by genetic manipulation (receptor knockout mice) or by pharmacological blockade of the GABAA and GABAB receptors. Embryonic GABAA receptor antagonism caused a decrease in the number of neurons that expressed estrogen receptor α in and around the PVN. In female but not male mice lacking GABAB receptors, the cytoarchitecture of the PVN was altered. Specifically, estrogen receptor containing cells were misplaced and corticotropin releasing hormone was increased. Animals treated with a GABAB receptor antagonist during embryonic development copied the phenotype of receptor knockout mice. The in vivo effect of GABA signaling on cell placement was investigated in vitro with organotypic slice fluorescence video microscopy. Again only in females, blockade of the GABAB receptor caused neurons to increase migration speed. Thus GABA acts to restrict cells from moving outside of the PVN. When the GABAB receptor is antagonized, cells migrate outside of the PVN. To determine the consequence of an animal having altered PVN development, animals treated as embryos with the GABAB receptor antagonist were subjected to a battery of behavior tests as adults. Interestingly, females treated embryonically with CGP 55845 displayed an increased anxiety-like phenotype (female specific disorder) while males treated with the same compound displayed a hyperactivity-like phenotype (male specific disorder). Independent of sex, animals treated as embryos with the GABAB receptor antagonist displayed decreased depression-like behaviors and had a less robust stress response compared to vehicle treated animals. This work highlights the importance of GABA signaling in PVN development and the dependence of complex adult behaviors on embryonic brain organization as GABA receptor antagonism limited to a specific critical time period during embryonic development recreated cytoarchitectural and behavioral phenotypes of GABA receptor knockout mice.
Keywords: anxiety; migration; hypothalamus; depression